Cancer Incidence and Mortality in Ardabil: Report of an Ongoing Population-Based Cancer Registry in Iran, 2004-2006 - M Babaei; H Jaafarzadeh; AR Sadjadi; F Samadi; A Yazdanbod; M Fallah; S Aghlmandi; R Ramezani; J Haukka; SH Hekmat; R Didevar; B Shokoohi; et al. (Tehran University of Medical Sciences, 2009)
"nBackground: Ardabil cancer registry is the first population-based cancer registry in Iran that was established in 2000. The first report from this registry revealed that Ardabil has one of the highest rate of gastric cardia cancer and the lowest rate of cervical cancer in the world. We aim to update the cancer incidence in this area by the second follow up report from this registry."nMethod: Data on all newly diagnosed cancer cases between 2004 and 2006 were actively collected. CanReg4 software was used for data entry and the data of cancer-related death were obtained from the comprehensive death registry system."nResults: More than 4300 new cases were registered during 3 years. Diagnosis of cancer was based on histopathology in 69%, clinical investigation 8%, clinical only 5%, and Death Certiﬁcate Only (DCO) in 18% of cases. In terms of age-standardized rate (/100,000), the five leading cancers in men (excluding skin cancer) were stomach (51.8), esophagus (19.5), bladder (13.1), lung and bronchus (10.8), and colorectal (9.6); in women, they were stomach (24.9), esophagus (19.7), breast (11.9), colon and rectum (7.4), and brain tumors (6.9). According to death registration data, upper gastrointestinal cancers constituted more than 43% of cancer-related death in Ardabil."nConclusions: The ASR for gastric cancer is among the highest rate for this cancer in male and female in the world. Most of the cancers, especially in female, have a significant increase compared to previous report from Ardabil. This is most likely due to the change in the registration practice.